(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to identify culture and its relationship to work stress in the general management of the North African Bank. This was achieved through the following steps: random sampling, which determined the descriptive composition due to its suitability to the nature of the study; the researcher developed a questionnaire; data collection was conducted, and the sample size was chosen to be 217 individuals, selected randomly. This represents 43.4% of the original population size of 500. The number of questionnaires used for analysis was 214, representing 42.8% of the original. The data were analyzed, and the research questions and hypotheses were tested using descriptive statistical analysis tools, which are the most common for this type of data.